2009
DOI: 10.1111/j.1365-2958.2009.06640.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide gene expression profiling and a forward genetic screen show that differential expression of the sodium ion transporter Ena21 contributes to the differential tolerance of Candida albicans and Candida dubliniensis to osmotic stress

Abstract: SummaryCandida albicans is more pathogenic than Candida dubliniensis. However, this disparity in virulence is surprising given the high level of sequence conservation and the wide range of phenotypic traits shared by these two species. Increased sensitivity to environmental stresses has been suggested to be a possible contributory factor to the lower virulence of C. dubliniensis. In this study, we investigated, in the first comparison of C. albicans and C. dubliniensis by transcriptional profiling, global gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Similar to SOD, catalase activity was signifi cantly (p < 0.01) higher in the sensitive and resistant C. albicans strains compared to the respective C. dubliniensis groups. In combination with the increased susceptibility of C. dubliniensis to hydrogen peroxide and macrophage killing, this result suggests that C. albicans is better protected from oxidative stress than C. dubliniensis, in accordance with the higher virulence of C. albicans 33,34,35 .…”
Section: Discussionsupporting
confidence: 59%
“…Similar to SOD, catalase activity was signifi cantly (p < 0.01) higher in the sensitive and resistant C. albicans strains compared to the respective C. dubliniensis groups. In combination with the increased susceptibility of C. dubliniensis to hydrogen peroxide and macrophage killing, this result suggests that C. albicans is better protected from oxidative stress than C. dubliniensis, in accordance with the higher virulence of C. albicans 33,34,35 .…”
Section: Discussionsupporting
confidence: 59%
“…These observations suggest a general role for calcineurin in controlling Ca 2ϩ homeostasis. Recently, Enjalbert et al showed that C. dubliniensis is Na ϩ hypersensitive compared with C. albicans (31). Thus, it is of interest to investigate the potential roles of calcineurin in Na ϩ , Ca 2ϩ , and Mn 2ϩ homeostasis in C. dubliniensis.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of Wor1 (246) and Ste2 (271) supports the hypothesis that switching emerged in the ancestor of C. albicans and C. dubliniensis. It is not clear whether this ancestor was highly pathogenic (like C. albicans) or relatively attenuated (like C. dubliniensis), although recent evidence suggests that lack of pathogenesis in C. dubliniensis may result from gene loss or changes in regulatory pathways (66,117,184). White-opaque switching is not needed for pathogenesis in C. tropicalis and C. parapsilosis, which presumably also have a long association with the human host.…”
Section: Saccharomyces Cerevisiae and Candida Glabratamentioning
confidence: 95%